Removal and Mark–Recapture Methods for Estimating Abundance: Empirical and Simulation Results for Mottled Sculpin in Streams. (30th January 2015) - Ruetz, Carl R.; Harris, Brandon S.; McNair, James N.; Homola, Jared J.
Abstract: Most studies that investigate biases in stream fish abundance estimators focus on salmonines, yet nongame species comprise a major portion of fish assemblages. We evaluated mark–recapture (the Lincoln–Petersen estimator with Chapman correction) and removal (constant capture probability and generalized removal estimators) methods for estimating abundance of Mottled Sculpin Cottus bairdii, and we tested whether assumptions of the abundance estimators (i.e., the population is closed during sampling; and marks are detected) were reasonable. Over 2‐d periods, fish in eight streams were sampled by using backpack electrofishing in 90‐m reaches (each divided into three 30‐m subreaches) to assess movement. Removal abundance estimates were significantly lower than mark–recapture estimates. Moreover, removal estimates were 52% lower than the known number of marked individuals, likely because capture probability ( q ) was low and declined with subsequent sampling passes. Survival of fish held in cages was 100%; there were no undetected marks among fish held overnight. For all streams combined, 11% of recaptured fish that were marked in the core subreach were recaptured on day 2 in an adjoining subreach. In five of the eight study streams, movement of marked fish from the core subreach was not detected, suggesting that in most streams the population was closed to movement. Using computer simulations, we found that low numbers of recaptures (mean < 6) negatively biased the mark–recapture estimator; however, the estimator was positively biased when the study population was open to movement—meaning that marked and unmarked fish were lost from the study reach as new, unmarked fish entered. Our results indicate that the removal estimator was negatively biased. We recommend using the mark–recapture method to estimate abundance when q is low (e.g., 0.21 in our study), with the caveat that study reach length must be sufficient to minimize fish movement across reach boundaries when block nets cannot be maintained between sampling events. Received January 14, 2014; accepted September 22, 2014